A preliminary study on the unhelpful thoughts and beliefs about stuttering (UTBAS) questionnaire in Croatia - Klarin, Ena (Array, 2018)
Along with disrupted speech fluency, people who stutter often develop a fear of speaking or fear of social situations that may lead to the emergence of social anxiety disorder. This has been the subject of numerous studies during recent decades, and specific questionnaires have been developed to assess relationships between stuttering and anxiety. The Unhelpful Thoughts and Beliefs About Stuttering (UTBAS) Questionnaire (St Clare et al. 2009) was developed recently and has been applied to evaluate the frequency and belief in thoughts about stuttering and the degree of anxiety induced by such thoughts. The aim of our preliminary study was to test the Croatian translation of the UTBAS (UTBAS-C) on people who stutter and those who do not stutter and to determine whether there is a statistically significant difference between these two groups, i.e. whether people who stutter are more socially anxious than people who do not stutter. Participants were 16 adults who stutter and 16 controls with normal fluence, aged 18-40 years. Because the results were not distributed normally, all data were analyzed with a non-parametric statistical method. The results showed a statistically significant difference between adults who stutter and those who do not. People who stutter had higher total scores on the Questionnaire, i.e. they are more socially anxious or have more negative thoughts and beliefs regarding speech-related situations than fluent adults. The results of our preliminary study are not unexpected and are consistent with most previous studies on the relationship between stuttering and anxiety. However, as there is a lack of specific instruments in the Croatian language that can be used in diagnosing adults who stutter, especially their attitudes and emotions, our translation of and further research on the UTBAS should help to fill that absence.